Praktik â€œPR Excellentâ€ Humas Pemerintah Daerah - Ajianto, Imon Dwi Budi; Kriyantono, Rachmat; Wulandari, Maulina Pia (ARISTO, 2018)
This study aims to describes the implications of the issuance of the Regulation of the Minister of Communication and Information Technology (Permenkominfo) no. 14/2016 on Local Government PR, especially districts / municipalities. Researcher explore how the perception of Government PR Officials, how the placement of Local Government PR on thestructure of Local Government Organization (OPD) and how the practice excellent PR by Local Government PR based on the principles of Excellence Theory with the implementation of Permenkominfo regulating the form, type, nomenclature, merging affairs, organizational structure, duties and functions of Field of Communication and Information. The Excellence Theory is one of the theories in the field of PR studies and is an effective standard of PR andexplains the ideal PR characteristics in an organization. Descriptive qualitative research method with in-depth interview data collection technique to the Communication and Information Management Officers and completed with document tracking. The results showed that the Communication and Information Management Officers have understood theregulation. However, not all Local Government have merged PR Division in the Dinkominfoas the implementation of Permenkominfo no. 14/2016. Placement of Local Government PRstill variations in OPD structure of each Local Government. Although it is found that theexcellent PR practice in general is good, but coordination needs to be done so that there is nooverlapping in task distribution in Field of Communication and Information Management in Local Government.